1990
DOI: 10.1152/jappl.1990.69.3.1165
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of training in humans: a 31P-MRS study

Abstract: The purpose of this study was to determine the feasibility of measuring with 31P nuclear magnetic resonance the effects of an endurance training program on the high-energy phosphate metabolism of exercising human skeletal muscle. The system used included a 1.9-T 30-cm-bore Oxford Systems superconducting magnet, a PhosphoEnergetics spectrometer, and a modified Cybex isokinetic ergometer. Seven healthy human volunteers exercised their wrist flexor muscles 20 min/day 5 days/wk for 8 wk. Testing before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 0 publications
5
31
0
Order By: Relevance
“…Imaging studies of PCr metabolism have been used to measure the effects of exercise on bioenergetic capacity (24). To enrich our interpretation of CrCEST imaging findings, we performed detailed analyses of the association between habitual intentional exercise, captured by the validated physical activity data collection instrument (25), and the imaging parameters measured.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies of PCr metabolism have been used to measure the effects of exercise on bioenergetic capacity (24). To enrich our interpretation of CrCEST imaging findings, we performed detailed analyses of the association between habitual intentional exercise, captured by the validated physical activity data collection instrument (25), and the imaging parameters measured.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the second major result ofthese experiments is that the PCr recovery time course differed among the subjects by metabolic energy supply (ATP synthesis). Differences in sustainable human muscle performance have been attributed solely to the oxidative capacity of the muscle (7,8). Our goal was to test quantitatively in intact human muscle for variation in contractile cost as well.…”
Section: Methodsmentioning
confidence: 99%
“…Recent 31P NMR studies have suggested that metabolic differences exist among fibers within human muscle (5,6) and between muscles of individuals at distinct training levels (7,8). However, it is not clear whether the fibers also differ in contractile costs in humans.…”
mentioning
confidence: 99%
“…Interpretation of these studies is, however, complicated by the fact that the anatomy of the forearm flexor muscles-macroscopic intra-and intermuscular heterogeneity, as well as the dimensions of the various muscle groups-could not be properly taken into account in the design of the voluntary exercise regimen and/or in the choice of the diameter of the surface coil because no MRI capability was available in these studies. As a result, mechanical and metabolic data were often not obtained from the same population of muscle fibers in these studies (1)(2)(3)(4)(5)(6)(7)(8)(9). Correlation of mechanical and metabolic data in these studies would thus be valid i f and only i f the contribution by fibers within the sampled muscle mass to the overall mechanical output was both representative for the total population of fibers activated by the exercise regimen as well as uniform among fibers within the metabolically sampled muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…A recently reported alternative experimental design for 31P MRS studies of human forearm muscle employing involuntary exercise by percutaneous nerve stimulation is based on this concept (10). However, with regard to voluntary handgrip or bulb-squeezing exercise protocols, recent IH MRI (11,12) and 31P chemical shift imaging (13) studies of fiber activity in forearm flexor muscles associated with these exercise regimens demonstrated great variation in fiber activity, suggesting the observed mechanical and metabolic data in previously reported 31P MRS surface coil studies may have come from different muscle groups (1)(2)(3)(4)(5)(6)(7)(8)(9). This may explain the interesting finding in two previous studies of human finger flexor muscle that the metabolic response to a standard voluntary exercise test was highly variable between different normal subjects (2, 3).…”
Section: Introductionmentioning
confidence: 99%